ANALISIS EFEKTIVITAS BERTAHAN PEMAIN SEPAK BOLA PADA TIMNAS SEPAK BOLA INDONESIA PADA SEA GAMES 2011, 2013 DAN 2019. - Zaqi Amirul Hanafiah, - (2021)
This study aims to analyze the performance of the Indonesian football team's defense effectiveness at the 2011 Sea Games, 2013 and 2019. This research is a descriptive study using an ex-post facto design, data collection techniques for defense effectiveness performance data analysis of marine matches using the GPAI instrument. The subjects in this study used total sampling, namely the video of the final match of the Indonesian national team in 2011, 2013 and 2019. The data collected will be analyzed using GPAI, then processed in SPSS version 26 with descriptive statistics. Normality test using Shapiro-Wilk, homogeneity test using One-Way Anova and hypothesis testing using Independent sample T-Test. Based on the results of research and discussion, it was found that the Indonesian national team's defense, the level of error (effective error) on the performance of the Indonesian national team was moderate. Keyword : defense effectiveness, performance, soccer